In Ukraine, the US is dragging us towards war with Russia - Pilger, John (The Guardian, 2014)
John Pilger: Washington's role in Ukraine, and its backing for the regime's neo-Nazis, has huge implications for the rest of the world
Keywords: Barack Obama; Europe; Foreign policy; Politics; Russia; UK news; US foreign policy; Ukraine; Vladimir Putin; William Hague; World news